A Study of Agricultural Activities in Nalanda District of Bihar - Sagar, Sandip (Journal of Advanced Research in Journalism & Mass Communication, 2019)
Since the inception of green-revolution in India, there is a drastic change in the pattern of crops grown in the country. Rising population pressure has forced to grow, food-crops and thus leading to an increase in cropping area. There is an upward trend in population and productivity of food-grains. Wheat and rice have experienced tremendous growth followed by vegetable production. However, this is not the trend with oil seeds, which is observing a fall in production and productivity. How to cite this article: Sagar S. A Study of Agricultural Activities in Nalanda District of Bihar. J Adv Res Jrnl Mass Comm 2019; 6(4): 29-32. DOI: https://doi.org/10.24321/2395.3810.201910